From the Vineyard to the Winery: How Microbial Ecology Drives Regional Distinctiveness of Wine - Liu, Di; Zhang, Pangzhen; Chen, Deli; Howell, Kate (Frontiers in Microbiology, 2019)
Wine production is a complex process from the vineyard to the winery. On this journey, microbes play a decisive role. From the environment where the vines grow, encompassing soil, topography, weather and climate through to management practices in vineyards, the microbes present can potentially change the composition of wine. Introduction of grapes into the winery and the start of winemaking processes modify microbial communities further. Recent advances in next-generation sequencing technology have progressed our understanding of microbial communities associated with grapes and fermentations. We now have a finer appreciation of microbial diversity across wine producing regions to begin to understand how diversity can contribute to wine quality and style characteristics. In this review, we highlight literature surrounding wine-related microorganisms and how these affect factors interact with and shape microbial communities and contribute to wine quality. By discussing the geography, climate and soil of environments and viticulture and winemaking practices, we claim microbial biogeography as a new perspective to impact wine quality and regionality. Depending on geospatial scales, habitats, and taxa, the microbial community respond to local conditions. We discuss the effect of a changing climate on local conditions and how this may alter microbial diversity and thus wine style. With increasing understanding of microbial diversity and their effects on wine fermentation, wine production can be optimised with enhancing the expression of regional characteristics by understanding and managing the microbes present.